2001
DOI: 10.1055/s-2001-15122
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Vascular Endothelial Growth Factor and Advanced Glycation End Products in Aqueous Humor of Patients With Diabetic Retinopathy

Abstract: Clinical studies have shown a relationship between diabetic retinopathy and vascular endothelial growth factor (VEGF) levels in ocular fluid. Advanced glycation end products (AGEs) have been implicated in diabetes complications, including diabetic retinopathy. Nepsilon-(carboxymethyl) lysine (CML) is a glycoxidation product that may be a marker of oxidative stress. In this study, we used enzyme-linked immunosorbent assays to determine the levels of VEGF, non-CML AGE and CML in the aqueous humor and serum of 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…They showed a highly significant reduction in the serum VEGF compared with their values before PRP performance (Table 7). These observations agreed with the findings of Lip et al, 49 Shinoda et al, 50 and Endo et al, 51 who detected a significant reduction in serum VEGF in a studied group of patients with PDR when performed effective PRP in 4 months follow-up.…”
Section: Eyesupporting
confidence: 83%
See 1 more Smart Citation
“…They showed a highly significant reduction in the serum VEGF compared with their values before PRP performance (Table 7). These observations agreed with the findings of Lip et al, 49 Shinoda et al, 50 and Endo et al, 51 who detected a significant reduction in serum VEGF in a studied group of patients with PDR when performed effective PRP in 4 months follow-up.…”
Section: Eyesupporting
confidence: 83%
“…In addition, PRP may cause ablation of many retinal cells capable of secreting VEGF such as retinal pigment epithelial ceils, pericytes, endothelial cells, Muller cells, and astrocytes. 37,51 …”
Section: Eyementioning
confidence: 99%
“…This immunohistochemical study showed that AGE immunoreactivity was detectable in the vitreous of diabetic eyes, suggesting that AGE can be secreted into intraocular fluid. In addition, Endo et al demonstrated that AGE concentration was increased in the aqueous humor in diabetic patients without retinopathy [11]. This study clearly demonstrated that AGE accumulation was marked in the iris and ciliary body stroma of diabetic eyes, indicating that the high concentration of AGE in the aqueous humor is related to the accumulated AGE in the iris and ciliary body.…”
Section: Discussionsupporting
confidence: 49%
“…High concentrations of AGE have been observed in the vitreous of patients with diabetic retinopathy [11,12,18]. This immunohistochemical study showed that AGE immunoreactivity was detectable in the vitreous of diabetic eyes, suggesting that AGE can be secreted into intraocular fluid.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation